ANALISIS KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PENGUNJUNG BADAN PERPUSTAKAAN DAN ARSIP DAERAH PROVINSI KALIMANTAN SELATAN - Penta Lestarini Budiati; Khairullah - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2015)
Abstract, This research aimed to analyze the level of visitor satisfaction when seen from the quality of service that earned the visitors with five determinants of quality of service as a benchmark the quality of service. The population in this research is that people who have been to the Library and Archives of South Kalimantan Province in 2014, samples were taken with a non-probability sampling method as many as 100 visitors. Further analysis of data using analysis techniques IPA (Importance-Performance Analysis). The results showed that the overall expectations of library visitors Library and Archives of South Kalimantan Province have not been met.